New Immunological Markers in Chromoblastomycosis—The Importance of PD-1 and PD-L1 Molecules in Human Infection - Cavallone, Italo N. [UNESP]; Belda, Walter; de Carvalho, Caroline Heleno C.; Laurenti, Marcia D.; Passero, Luiz Felipe D. [UNESP] (MDPI, 2023)
The pathogenesis of chromoblastomycosis (CBM) is associated with Th2 and/or T regulatory immune responses, while resistance is associated with a Th1 response. However, even in the presence of IFN-γ, fungi persist in the lesions, and the reason for this persistence is unknown. To clarify the factors associated with pathogenesis, this study aimed to determine the polarization of the cellular immune response and the densities of cells that express markers of exhaustion in the skin of CBM patients. In the skin of patients with CBM, a moderate inflammatory infiltrate was observed, characterized primarily by the occurrence of histiocytes. Analysis of fungal density allowed us to divide patients into groups that exhibited low and high fungal densities; however, the intensity of the inflammatory response was not related to mycotic loads. Furthermore, patients with CBM exhibited a significant increase in the number of CD4+ and CD8+ cells associated with a high density of IL-10-, IL-17-, and IFN-γ-producing cells, indicating the presence of a chronic and mixed cellular immune response, which was also independent of fungal load. A significant increase in the number of PD-1+ and PD-L1+ cells was observed, which may be associated with the maintenance of the fungus in the skin and the progression of the disease.
Keywords: cell exhaustion; chromoblastomycosis; immunological response; melanized fungi; PD-1; PD-L1